Piloting a scale of social integration in South African organisations - Young, Margaret (Organisational Psychology, 2020)
“Social integration” is a construct referred to in workgroup and organisational research, in particular in research focused on understanding workplace diversity. The present research examined how the social integration construct could be more clearly conceptualised and measured in the South African context. Guided by Hinkin’s (1998) scale development framework, the research seeks to contribute to the early stages of the development of a scale of social integration, suited for use in South African workplaces. Items were generated theoretically, leading to a final pool of 72 items. 620 usable responses were received from individuals employed in organisations in South Africa and this sample was randomly split into two samples of 310 participants each: a “calibration” and “validation” sample. On the calibration sample, exploratory factor analysis (EFA) was conducted in order to examine emerging first- and higher-order latent variable structures. EFA led to the development of a first-order, seven-factor model. Exploratory extension analysis generated three possible higher-order latent variable structures. Using confirmatory factor analysis (CFA), both the first- and higher-order models were fitted to the “validation” sample to test if the models generalised to a second sample drawn from the same population. Results indicated that the first-order model demonstrated an adequate fit, as well as two of the three higher-order models. The fit of these two higher-order models did not differ significantly. Post-hoc analyses determined that, while social integration can be considered a meaningful higherorder construct, the construct has theoretical rather than practical relevance for researchers. Responses to the proposed scale of social integration should be interpreted at the level of the identified first-order constructs rather than as a single scale representing the higher order, abstract social integration construct. The generalisability and contextual nature of the research findings, suggestions for future research, and the theoretical and practical limitations of the present research are discussed.